Comprensión lectora y rendimiento académico en alumnos de 5° grado de primaria de una institución educativa policial del Callao - Guillén Salazar, Julia Roxana (2012)
It analyzed the relation between reading comprehension and academic performance on students of fifth grade from a police educational institution of Callao. Not experimental type of studying and descriptive correlational design. To the sample of 140 male and female students were applied Reading Comprehension Test of Linguistic Complexity Progressive (LCP) of parallel forms, A Form Level 5 of Allende, Condemarín and Milicic (1991) adapted by Delgado (2005) to know reading comprehension levels and for academic performance it used the Official Record and Final Assessment Act. Results showed that predominate a very low level of reading comprehension and the average in academic performance. It was applied Spearman test for the inferential analysis. It was confirmed the general hypothesis, otherwise, there is a positive and significant relation between both variables, the conclusion is that a great reading comprehension, a greater academic performance.